Formation of humoral and cellular immunity to measles vaccine in adults - A. P. Toptygina (Sankt-Peterburg : NIIÈM imeni Pastera, 2020)
Despite adherence to the policy of mass measles vaccination in the majority of countries, this infection still remains far from being fully eradicated. Measles outbreaks are reported worldwide, when the vast majority of cases are recorded in subjects of 18—35 years of age. Studies on assessing measles IgG antibody level in different regions of Russia reveal increased percentage of measles seronegative subjects among young adults. Current study was aimed at investigating formation of humoral and cellular immunity after measles vaccination in seronegative adults aged 18 to 30 years old. There were enrolled 50 measles seronegative healthy volunteers aged 18 to 30 years old. Level of anti-measles IgM and IgG antibodies was measured by ELISA (Vector-Best, Russia). Subclasses of measles specific IgG antibodies were analyzed by ELISA, by replacing IgG conjugate for IgG1, IgG2, IgG3, IgG4 conjugates, whereas measles specific IgA antibodies were estimated by ELISA with IgA conjugate (Polygnost, Russia) at a concentration of 1 μg/ml. Antibody avidity was assessed by ELISA (Euroimmun, Germany). Cell-mediated measles immunity was estimated by CD107a surface expression on CD8hi T cell subset stimulated by measles virus-derived antigens. A specific cellular response to measles antigens before vaccination was detected in 50% of examined subjects, whereas 40% samples showed no signs of cellular immune response, with 10% of remaining cases described as equivocal. It was found that 6 weeks after vaccination all vaccinated subjects developed measles specific IgG antibodies at protective level reaching 1.33 (0.85—1.82) IU/ml [Me (LQ—UQ)]. Anti-measles IgA antibodies were of 0.655 (0.423—1.208) IU/ml [Me (LQ—UQ)]. However, no measles specific IgM antibodies were detected 6 weeks after vaccination. In addition, primary type of immune response (dominant low-avidity anti-measles antibodies IgG3 subclass) to measles vaccination was observed in 24 out of 50 subjects, whereas 26 subjects developed secondary type of immune response (high-avidity anti-measles antibodies dominated by IgG1 subclass). A measles specific cellular immune response was observed in 47 of the 50 examined subjects, and in 3 volunteers it was equivocal. Further analysis revealed a cohort of subjects who were not vaccinated against measles (18 subjects), although 60% of them provided medical record on previous dual measles vaccination occurred in childhood. Another cohort consisted of subjects who had medical record of measles vaccination in childhood (32 subjects), but lost protective measles antibodies produced by plasma cells (23 subjects), and memory T cells (3 subjects), or measles antibodies and memory B cells (6 subjects) over time. Such pattern evidences that measles-specific cellular and humoral arms immune responses were developed and maintained independently of each other.